Innovative Strategies for Sustainable Tourism Destinations in Denpasar Through the Concept of Community-Based Placemaking - Nurwarsih, Ni Wayan; Darmawan, I Gede Surya; Parwata, I Wayan (ASTONJADRO, 2025)
This research explores the challenges of integrating spiritual and cultural values into public spaces and addressing environmental and social issues in Denpasar, a city under urbanization and mass tourism pressures. The study aims to explore innovative strategies for sustainable tourism in Denpasar through the concept of community-based placemaking, employing both top-down and bottom-up approaches to create meaningful spaces. A qualitative approach was used, with data collected through in-depth interviews, participatory observations, and document analysis, focusing on case studies in one traditional village in each of Denpasar’s four districts. The research highlights the role of local communities, cultural integration, and environmental sustainability. Findings reveal that the bottom-up approach in placemaking enhances community engagement and cultural authenticity, while the top-down approach, although efficient, requires better integration of local values. The study concludes that a collaborative framework involving local communities, the government, and the private sector is essential for creating sustainable tourism destinations. This research contributes to the field by offering practical strategies for culturally and environmentally sensitive placemaking, particularly in urban contexts.